Rancang bangun sistem penangkap sampah Daerah Aliran Sungai (DAS) berbasis integrasi screw conveyor dan sistem pemantauan menggunakan Internet of Things (IoT) - Putu Brahmanda Sudarsana; I Made Putra Arya Winata; I D. G. Ary Subagia (Jurnal Energi Dan Manufaktur, 2021)
Waste material flowing in rivers creates several problems in various aspects, especially in environmental aspects. One of the waste-capturing mechanisms which is widely applied is the trash rack. However, studies show that trash racks have the potential to block river flow which increases the risk of flooding. This study proposes a screw conveyor-based waste capturing mechanism with a modification of the blade’s design resembling a trash rack and integrated with monitoring system using the internet of things. The research was conducted through three methods of virtual prototyping, the CAD (Computer-Aided Design) design method through calculation of machine elements and 3-dimensional design process using Autodesk Inventor Professional 2018 software, the design analysis method which includes computational fluid dynamics analysis and three-dimensional stress analysis using ANSYS software, as well as methods for designing and testing monitoring systems using the open-source NodeMCU board and Google Firebase real-time database. The result obtained from this research are the design and specifications of screw conveyor components, v-belt transmission systems, ball contact bearings, and electric motors with a waste-capturing capacity of 0.368 m3/s. The results of the design validation show that the velocity of water flowing through the design geometry is not significantly reduced and the design is able to withstand a combination of self-load and pressure loads due to water flow. The monitoring website has been able to display real-time sensor-acquired data.